1998
DOI: 10.1152/ajplung.1998.274.5.l750
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of rat lung acidic Ca2+-independent PLA2and its organ distribution

Abstract: A clone for a rat acidic Ca2+-independent phospholipase A2(aiPLA2) was isolated from a cDNA library prepared from rat granular pneumocytes with a probe based on the human aiPLA2 sequence (T. S. Kim, C. S. Sundaresh, S. I. Feinstein, C. Dodia, W. R. Skach, M. K. Jain, T. Nagase, N. Seki, K. Ishikawa, N. Nomura, and A. B. Fisher. J. Biol. Chem. 272: 2542–2550, 1997). In addition, a consensus sequence for mouse aiPLA2 was constructed from several mouse cDNA clones in the GenBank and dbEST databases. Each sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
141
1
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(150 citation statements)
references
References 28 publications
6
141
1
2
Order By: Relevance
“…For analysis by SDS͞PAGE (12% Tris-Glycine, 1 mm) with the Nu-PAGE system (Invitrogen), protein was solubilized with 4ϫ sample buffer and boiled for 5 min before loading. After electrophoretic resolution, the proteins were electroblotted to Immobilon-P membranes (Millipore) and blocked for 1 h in Tris-buffered saline with 0.05% Tween 20 (TBST) containing 5% nonfat dry milk, and membranes were probed with either a monoclonal or a polyclonal antipeptide antibody against recombinant protein (7,17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For analysis by SDS͞PAGE (12% Tris-Glycine, 1 mm) with the Nu-PAGE system (Invitrogen), protein was solubilized with 4ϫ sample buffer and boiled for 5 min before loading. After electrophoretic resolution, the proteins were electroblotted to Immobilon-P membranes (Millipore) and blocked for 1 h in Tris-buffered saline with 0.05% Tween 20 (TBST) containing 5% nonfat dry milk, and membranes were probed with either a monoclonal or a polyclonal antipeptide antibody against recombinant protein (7,17).…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, 1-cys peroxiredoxin (1-cysPrx or Prx VI) † has a single conserved cysteine (5) and does not use thioredoxin as reductant (5,6). This peroxiredoxin is expressed in all tissues but at particularly high levels in brain, eye, testes, and lung (2,7,8). Expression of 1-cysPrx protein or mRNA is decreased in a mouse that is susceptible to experimental atherosclerosis (9) and is elevated in brains of patients with Parkinsonian dementia (10), sporadic Creutzfeldt-Jacob disease (11), and Pick disease (12), in lungs from newborns (13), in malignant mesothelioma (14), in the healing edge of skin wounds (15), and in experimental cellular premature senescence (16).…”
mentioning
confidence: 99%
“…Expression of a green fluorophore (either ZsGreen1 or GFP) was used as a transfection efficiency control, and hydroethidine (red) was used to detect ROS. The pIRES-ZsGreen vector encoded mouse Prdx6, whereas the GFP-C1 vector encoded rat Prdx6; the deduced Prdx6 protein sequences for the two species show 94% amino acid identity (20). Transfection efficiency in these cells using the Amaxa electroporation system was ϳ70%.…”
Section: Ros Production With Ang II Treatment Of Lung Endothelium In mentioning
confidence: 99%
“…5, A and B). DISCUSSION 1-cysPrx is a recently described antioxidant enzyme member of the Prx family that is expressed at relatively high levels in the lung (14). In lung epithelial cell lines, overexpression of 1-cysPrx protein was shown to increase the ability of these cells to degrade H 2 O 2 and to protect them against oxidantinduced plasma membrane damage (17), whereas treatment with an antisense oligonucleotide to 1-cysPrx resulted in lipid peroxidation and apoptosis (20).…”
Section: Lung Distribution Of Gene Transfermentioning
confidence: 99%
“…Peroxiredoxin VI or 1-cys peroxiredoxin (1-cysPrx) has a single redox-active cysteine and utilizes GSH to catalyze the reduction of H 2 O 2 and organic hydroperoxides including phospholipid hydroperoxides (8). 1-cysPrx is highly enriched in the lung compared with other organs and is especially expressed in Clara and alveolar epithelial type II cells (14). Previous studies have demonstrated that overexpression of 1-cysPrx in NIH 3T3 cells enhances their ability to reduce H 2 O 2 and protects their glutamine synthetase against H 2 O 2 -mediated inactivation (12).…”
mentioning
confidence: 99%